2014
DOI: 10.1080/09712119.2014.928626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Macsumsuk®supplementation on growth performance, haematological parameters, disease resistance and body composition of juvenile Nile tilapia,Oreochromis niloticusL.

Abstract: An eight-week feeding trial was conducted to evaluate the effects of dietary Macsumsuk ® supplementation on growth performance, haematological parameters, disease resistance and body composition of juvenile Nile tilapia, Oreochromis niloticus. A total of 375 fish averaging 1.0 ± 0.05 g (mean ± SD) were randomly distributed into 15 tanks in groups of 25, and each tank was then randomly assigned to one of three replicates of five diets containing 0(M 0 ), 0.3(M 0.3 ), 0.6(M 0.6 ), 1.2(M 1.2 ) and 2.4(M 2.4 )% di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Moreover, fish fed the YM, BG and CONT diets did not show significant differences in terms of FE and PER. The observations with the SG diet is comparable to the findings by Lee et al (2015b) and Won et al (2017) with Song-gang Ò stone and yellow loess, respectively, in rainbow trout Oncorhynchus mykiss as well as Shahkar et al (2015) with Macsumsuk Ò in Nile tilapia Oreochromis niloticus. Growth and feed efficiency improved in olive flounder Paralichthys olivaceus fed a combination of b-glucan and BAISM-contained diets (Yoo et al 2007).…”
Section: Growthsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, fish fed the YM, BG and CONT diets did not show significant differences in terms of FE and PER. The observations with the SG diet is comparable to the findings by Lee et al (2015b) and Won et al (2017) with Song-gang Ò stone and yellow loess, respectively, in rainbow trout Oncorhynchus mykiss as well as Shahkar et al (2015) with Macsumsuk Ò in Nile tilapia Oreochromis niloticus. Growth and feed efficiency improved in olive flounder Paralichthys olivaceus fed a combination of b-glucan and BAISM-contained diets (Yoo et al 2007).…”
Section: Growthsupporting
confidence: 75%
“…It is the second freshwater farmed fish species with a production of 4607 tons in the Republic of Korea in 2014(FAO 2016. Several dietary additives have been identified to promote growth and immune responses in the aquaculture industry (Choi et al 2004;Ai et al 2007;Yoo et al 2007;NRC 2011;Güroy et al 2014;Lee et al 2015b;Shahkar et al 2015); however, each dietary additive could produce different levels of responses in individual fish species and contribute differently to feed cost. In this regard, the effects of dietary additives from mineral sources have not yet been investigated in Amur catfish.…”
mentioning
confidence: 99%
“…alga Schizochytrium sp. is one of the most consumed by marine fish and have potential for its use in freshwater species feeding (Li, Robinson, Tucker, Manning, & Khoo, 2009;Saiyasaeng, Yuangsoi, Wiriyapattanasub, & Wongmaneeprateep, 2014;Sarker, Gamble, Kelson, & Kapuscinski, 2015;Sarker, Kapuscinski, Lanois, Livesey, & Bernhard, 2016), and has favourable nutritional characteristics to be introduced in the production of fish diets, since it has approximately 25% of DHA in its composition.…”
mentioning
confidence: 99%
“…Macsumsuk ® is in kaolinite family can be classified as clay minerals containing SiO 2 (73.0%), Al 2 O 3 (13.8%), Fe 2 O 3 (3.04%) and CaO (2.34%), and pH value is 10; it radiates far infrared rays of 108–133 Hz (Kim et al, ). Macsumsuk ® is purified through ore‐dressing, burning out and powdering after mining from Macsumsuk ® mines, which is being used widely from high‐tech industrial materials to the household as a medicine and for medical products and the purification of water and air (Shahkar, Park, Lee, Kwak, & Bai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality characters like low cooking loss and cholesterol level and high palatability were improved by Macsumsuk ® and/or herb mixtures in pork diets (Kim et al, ). Nevertheless, Shahkar et al () observed improved growth performances, haematology and innate immunity for Edwardsiella tarda infection in Nile tilapia ( Oreochromis niloticus ) by dietary Macsumsuk ® . Therefore, we aimed to examine the results of dietary administration of Macsumsuk ® on shrimp growth and stress tolerance as well as to understand the optimum dietary Macsumsuk ® level on growth of juvenile whiteleg shrimp, L. vannamei .…”
Section: Introductionmentioning
confidence: 99%